Effects on the ubiquitin proteasome system after closed soft-tissue trauma in rat skeletal muscle - Ponelies, Norbert; Gosenca, Darko; Ising, Nadine; Schoen, M.; Ruppel, K.; Vollmar, Brigitte; Obertacke, Udo (European journal of trauma and emergency surgery, 2011)
Previous studies have suggested that an increased catabolic stage of skeletal muscle in pathological situations is mainly a reflection of ubiquitin-proteasome system-controlled proteolysis. The proteolytic mechanisms that occur after local muscle trauma are poorly defined. We investigated the effects of closed soft-tissue trauma on ubiquitin-proteasome dependent protein breakdown in rats (n = 25). The enzymatic activities of the ubiquitination and proteasome reactions were both reduced (p < 0.05) immediately after contusion of the hind limb musculus extensor digitorum longus. The same effect was observed in extracts of lung tissue from the injured animals. Cellular levels of free and protein-conjugated ubiquitin were significantly elevated upon decreased proteolytic activity. Our data support an early-state anti-proteolytic role of the ubiquitin-proteasome pathway after local injury. This further implies that there is a yet-to-be elucidated complex regulatory mechanism of muscle regeneration that involves various proteolytic systems.
Gesehen am 05.01.2023